Pengungkapan Kinerja Sosial pada Aspek Sosial Instansi Pemerintah Daerah Melalui Laporan Keberlanjutan Berbasis Global Reporting Initiative : (Studi Kasus pada Pemerintah Kota Bandung) - Juan Hendrian Pratama; Syaiful Rahman Soenaria (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
Bandung City Government is a government agency that has not published its own sustainability report. The reason why this research was conducted on the social aspects of sustainability reporting at the Bandung City Government is because these government agencies and should be role models for sustainable development as they act according to the public interest and the first step to take responsibility for the social impacts caused by the Bandung City Government is to publish a sustainability report. This research was conducted over a period of time from September 2023 to March 2024, and was conducted using a single case study process with the Bandung City Government with the specific method of Action Research. This method involved asking people with capacity in the Bandung City Government who had intensive and in-depth knowledge of the aspects that needed to be disclosed in the sustainability report for data. Further documentation was also taken to prove that the information was valid. It is then reported in GRI 401, 402, 403, 404, 405, 406, 407 for social aspects. General indicators regarding all information that needs to be disclosed are in GRI 2 and 3. Based on the research conducted, it aims that the Bandung City Government can disclose material information regarding general and social impacts into the Sustainability Report, using the GRI Standards as guidelines.